A theoretical density functional theory calculation-based analysis of conformers of p-xylene - Suhail, Mohammad (European Journal of Chemistry, 2022)
Different conformers of many aliphatic compounds such as ethane, butane, cyclohexane and their derivatives have been studied to find the most reactive as well as the most stable conformer. For the first time, two conformers of p-xylene were found using theoretical DFT calculation and the vibrational modes, Raman activity, and other spectra of each conformer were also studied. The most significant data that clearly distinguished both conformers was depolarization spectra. Besides, many other parameters were found different in both conformers of p-xylene such as Mulliken charge’s, optimization energy, HOMO’s of both conformers. Also, the presented study predicts, why eclipsed conformer of p-xylene is more reactive than staggered conformer. The reactivity of the eclipsed form is explained on the basis of HOMO-LUMO energy gap. Also, the presented study opens the door for future work to be done because each conformer can produce a specific product. Moreover, the rates of reaction are also dependent on the conformers and their relative stability.